1997
DOI: 10.15517/rmta.v4i2.148
|View full text |Cite
|
Sign up to set email alerts
|

Analyis on the vascular epiphytes of tree ferns in a montane rain forest in Costa Rica

Abstract: The relationships between epiphytes and host specifity are known. We investigated the relation between specific epiphytes and tree fern trunks. Only some epiphytes are frequent or very frequent on tree ferns. Most of the epiphyte species are unspecific on these trunks. Blechnum fragile are the only found exclusively on tree ferns. We also observed different epiphyte communities dependent on the tree fern species and the morphology of the tree fern trunk. Resumen La relacin entre plantas epfitac y las plantas q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In tropical forests, Orchidaceae and Bromeliaceae prevail in the crown and ferns prevail in the forest understory and trunks (Krömer et al, 2007; Petter et al, 2016). The Orchidaceae family, one of the most abundant epiphytic families for either the Atlantic Forest (Freitas et al, 2016) and the world (Zotz, 2013b), was too underrepresented in other studies with tree ferns (Becker et al, 2015; Bittner & Trejos‐Zelaya, 1997; Schmitt & Windisch, 2005). This underrepresentation may occur as a result of chemical or biological processes that inhibit the establishment of the family on tree ferns (Benzing, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tropical forests, Orchidaceae and Bromeliaceae prevail in the crown and ferns prevail in the forest understory and trunks (Krömer et al, 2007; Petter et al, 2016). The Orchidaceae family, one of the most abundant epiphytic families for either the Atlantic Forest (Freitas et al, 2016) and the world (Zotz, 2013b), was too underrepresented in other studies with tree ferns (Becker et al, 2015; Bittner & Trejos‐Zelaya, 1997; Schmitt & Windisch, 2005). This underrepresentation may occur as a result of chemical or biological processes that inhibit the establishment of the family on tree ferns (Benzing, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The basal portion of tree ferns caudices is much older since these plants grow only a few centimeters per year (Bittner & Breckle, 1995; Schmitt & Windisch, 2006, 2012; Tanner, 1983). Therefore, it holds greater epiphytic abundance as this region is more likely to be colonized by epiphytes (Bittner & Trejos‐Zelaya, 1997; Gaxiola et al, 2008). We highlight that, despite some records of C. phalerata and A. setosa growing above 5 m, more than 75% of the individuals measured in the Atlantic rainforest were below 5 m high (Schwartz & Gasper, 2020), showing that our measured individuals—with 4 m high as an upper threshold—include mature individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most recent studies on the ecology, floristic, and diversity of epiphytic ferns were reported outside of the Malesian region (Bianchi and Kersten 2014;Chambers et al 2017;Díaz et al 2012;Eskova et al 2020;Gabriel y Galaân et al 2018, Gonzalez et al 2017Huang et al 2019;Klinghardt and Zotz 2021;Lu et al 2015;Machado et al 2016;Moulatlet et al 2019;Mountier et al 2018;Nagalingum et al 2015;Nettesheim et al 2014;Nitta et al 2020;Oldekop et al 2012;Pouteau et al 2016;Quaresma et al 2017;Ramírez-Barahona et al 2011;Riefner Jr. and Smith 2019;Sanger and Kirkpatrick 2015;Schmitt and Windisch 2010;Sugita et al 2013;Testo and Watkins 2013;Wagner et al 2015). Ecological studies dealing with the composition, community structure, and vertical distribution of epiphytic tree ferns outside of the Malesian region have been reported (Bittner and Trejos-Zelaya 1997;Roberts et al 2005;Fraga et al 2008;Scheider and Schmitt 2011). A study on the diversity and composition of the epiphytic vascular plant, including ferns, on tree ferns (Cyathea spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Tree ferns are part of tropical forest ecosystems and are hosts for many epiphyte species. The study of epiphytes and tree ferns as its host showed that tree ferns species and the morphology of their trunk influenced epiphytic plant communities [9]. The root mantles on trunk of tree ferns provided a more favourable microhabitat for epiphytic plant growth [10].…”
Section: Introductionmentioning
confidence: 99%